Application of SAK ETAP to The Financial Statements of KSP Syafit Mandiri Marawi Pinrang Based on Sharia Accounting - Annisa; Husain, Saddan (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2022)
This study aims to determine the suitability of the financial statements made by KSP Syafit Mandiri Marawi Pinrang with SAK ETAP and the use of Islamic accounting principles in the financial statements of KSP Syafit Mandiri Marawi Pinrang. This research is a type of qualitative research using a phenomenological approach in data collection. The data processed is the financial report of KSP Syafit Mandiri Marawi Pinrang in 2020. The data collection and processing techniques use the methods of observation, interviews, and documentation. The validity test of the data used is the credibility test. While the data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results showed that KSP Syafit Mandiri Marawi made a financial report consisting of a balance sheet, Remaining Operating Income (SHU) and SH distribution plans. So it can be concluded that the financial statements of KSP Syafit Mandiri Marawi Pinrang are not in accordance with SAK ETAP. In addition, there are naming of account posts that are not in accordance with SAK ETAP in the financial statements made. The financial statements made by KSP Syafit Mandiri Marawi Pinrang are in accordance with the principle of responsibility, the principle of justice but not yet fully in accordance with the principle of truth. This is because KSP Syafit Mandiri Marawi Pinrang does not make a cash flow report, a statement of changes in equity and notes to its financial statements. Keywords: SAK ETAP, Financial Statements, Sharia Accounting